Re-engineering the Neo-Modernist Hermeneutics for the Post-Truth Digital Sphere - Atoillah, Muhammad Agil; Saryulis, Muhammad Irham (An-Nur International Journal of Islamic Thought, 2025)
The intellectual legacy of Islamic Neo-Modernism, grounded in the hermeneutics of Fazlur Rahman and operationalized by Nurcholish Madjid and Abdurrahman Wahid, successfully transitioned Indonesia from authoritarianism to democracy by reconciling Islamic authenticity with pluralism. However, the efficacy of this "analog" framework in the digital era remains critically underexamined. This study investigates the structural compatibility between Neo-Modernist epistemology—characterized by "high-context" reasoning and historical regression—and the "low-context" architecture of contemporary social media platforms. It specifically interrogates why the proliferation of moderate (Wasaṭiyyah) content has failed to counteract the rise of digital radicalism. Adopting a "Techno-Hermeneutic" framework that synthesizes Rahman’s "Double Movement" theory with Media Ecology, this research employs a Critical Conceptual Synthesis design to scrutinize high-impact empirical data from 2018–2024. The analysis reveals a "Hermeneutic Short-Circuit": digital platforms structurally amputate the "First Movement" (historical regression) required by Neo-Modernist thought, rendering it incompatible with the "infinite scroll." Furthermore, findings indicate that algorithmic metrics actively penalize Madjid’s "psychological skepticism," transforming Civility into performative identity conflict. At the same time, the "globally legible" aesthetics of the algorithm displace Wahid’s Indigenization, creating a vacuum of rooted authority. The study concludes that the digital medium inherently erodes Neo-Modernist authority by favoring "burstiness" over "psychological skepticism." Consequently, simply increasing the volume of moderate content is futile. The survival of Civil Islam requires a radical re-engineering of hermeneutic methods toward "Indigenous Data Sovereignty" and algorithmic transparency, shifting the battleground from content production to infrastructure governance.